The Influence of Family, School, and Community Surrounding toward Gender Perception of Male and Female Student - Dya Rahayu, Rehasti; Wigna, Winati (Sodality: Jurnal Sosiologi Pedesaan, 2011)
The goals of this research are to analyze family, school, and society area that influence of student gender perception and then to know the different influence factors from it. This research has done in STEI TAZKIA. Generally, even though have the high education but the gender perception is still low. This reality has different with what happened in STEI TAZKIA. STEI TAZKIA students have the high gender perception. Those facts are the good reason to do research in STEI TAZKIA. The results of this research are student gender perceptions do not come from the family area, but student gender perception come from school and society area and there are different results from boy and girl students. The results of this research proofed that the influence boy students gender perception come from school area (from their teacher) and society area (from their friends), different with the girl students that the influence gender perception come from family area (from their mother).